In-Operando Measurement of Temperature Gradients in Cylindrical Lithium-Ion Cells during High-Current Discharge. (30th October 2014) - Waldmann, Thomas; Wohlfahrt-Mehrens, Margret
Abstract : The temperatures inside the jelly roll and on the surface of high-power 18650-type cells are investigated quantitatively. In-operando temperature measurements are conducted during discharge at rates in the range of 1C-12C. The experimental data are used to estimate local aging gradients inside the cell. The maximum temperatures on the cell housing and inside the jelly roll are correlated to the respective discharge currents, yielding clear linear dependencies over the whole current range. Using the collected data, a straightforward low-cost semi-empirical model is developed for prediction of the temperature rise inside cylindrical cells during discharge at different currents.